MODERN APPROACH TO OPTIMIZATION OF CHILDREN’S FEEDING ON THEIR FIRST YEAR OF LIFE - Е.А. Pyr'eva; V.I. Dronova (Вопросы современной педиатрии, 2011)
New approach to optimization of feeding of infants on their first year was regarded in this article. The role of probiotics in children’s health maintenance has been underlined in the article as well. Also there’s new information upon efficacy of a milk formula enriched with lactobacteria (Lactobacillus fermentum hereditum CECT5716), extracted from breast milk, in nourishment of infants receiving artificial formulas. Key words: children, probiotics, lactobacteria, feeding. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 130–132.)